PERBEDAAN SELF-REGULATED LEARNING DITINJAU DARI POLA ASUH ORANGTUA PADA SISWA KELAS VIII SMP FRANSISKUS DAN SMP PGRI 01 SEMARANG - Januardini, Lintang; Hartati, Sri; Astuti, Tri Puji (Faculty of Psychology, Diponegoro University, 2013)
Relationship between parents and adolescents influence achievement at school. The research was conducted to determine differences of self-regulated learning (SRL) in terms of parenting style. The population is 8th grade students of junior high school in SMP Fransiskus and SMP PGRI 01 Semarang. The hypothesis is there are differences of SRL in terms of parenting style. Parenting is overall characteristic of parent’s behavior on adolescents, including a response in the form of parental warmth, sensitivity and criticism, discipline, and involvement (control). Self-regulated learning is the ability of students to use metacognition, motivation and behavior to achieve learning goals. Method of data collection used two scales namely Parenting Scale and Self Regulated Learning scale. Parenting Scale consists of 42 aitem (α = 0.931) and the SRL scale consists of 37 aitem (α = 0.906). This study involved 208 students. Sampling technique carried out by cluster random sampling. Data analysis was performed by one way analysis of variance (one way-Anova). Based on the data analysis, obtained F count = 3152 with p = 0.029 (p<0.05). This result indicates that there are significant differences in SRL on students with the type of parenting authoritative, authoritarian, permissive, and neglect, so the hypothesis was accepted.Keywords: Parenting style, SRL, 8th grade students